The Structure and Ferroelectric Properties of Iron-Doped Lead Titanate - (:unkn) unknown (My University, 2014)
Multiferroics are a class of poorly understood, but technologically important materials. Lead(II) titanate (PbTiO$_3$) is a known perovskite ferroelectric. By doping PbTiO$_3$ with Fe$^{3+}$ at the Ti site, we produce the multiferroic PbTi$_{1-x}$Fe$_x$O$_3$ (PTFO). Using selected area electron diffraction on a transmission electron microscope, the structure of PTFO is investigated. Of particular interest is identifying the cubic-to-tetragonal transition at the Curie temperature. As the concentration of Fe increases, the crystal becomes more cubic and experiences a lower transition temperature. I also establish a procedure for preparing bulk PTFO samples for ferroelectric testing and present preliminary results establishing ferroelectricity in these PTFO samples. Ferroelectricity is determined by detecting the remanent polarization and switching voltage from ferroelectric hysteresis. A Radiant Technologies Precision LC loop-tracing assembly is used to test the samples for ferroelectric hysteresis.
Keywords: Ferroelectrics; Lead Titanate; Multiferroics